Gestión operativa-administrativa y su incidencia en el desempeño institucional de la unidad nacional de almacenamiento ubicada en el cantón Quevedo, provincia de Los Ríos, período 2011-2012. Manual de procedimientos - Guillin Llanos, Ximena Minshely (2013)
The present research was conducted at the Plant Silos Quevedo National Unity Storage located at Km 1 ½ road to Santo Domingo, an institution that was created on August 27, 2007 by Executive Order No. 589, the Econ. Rafael Correa Delgado, Constitutional President of the Republic whose mission is to be a support agency for small and medium farmers short cycle with integrated marketing services to regulate and monitor market prices through a storage infrastructure for agricultural products, ensuring food security and sovereignty. The main services provided plant silos are automatic weighing truck scales certified by the NIE, laboratory standards based on INEN, grain cleaning, grain drying and plant maintenance and preservation of the product.In Quevedo Canton area crop farming corn, rice and soybeans is highly productive, so that the level of satisfaction of farmers is reflected in the care and service provided by the staff. However to date the National Storage Unit Plant Quevedo and after the SWOT analysis, we have determined that its weaknesses consists lack of a procedures manual, a tool that detail how to perform a task or a particular job and allows evaluate staff performance indicators according de establecer efficiency, effectiveness, economics, ethics and ecology. From what I have proposed the design of a procedural manual in order to help improve administration in the management of resources and to serve as a guide for each and every one of the staff to identify their activities and responsibilities within this institution that serves the agricultural population of the canton and the surrounding areasTo establish the reality of the problem and how it manifests within the company conducted a field work consisted of: 1) Internal Control Questionnaire to establish the degree of confidence and risk of officials of the National Storage Unit , Surveys of farmers who were beneficiaries with the service of the Unit and the Chief Plant Interview with the goal of diagnosing collect accurate information and 2) Tabulation of results in order to proceed to the analysis and interpretation of data, and so establish the causes and conclusions on operational management issues and administrative and on this basis, issue relevant recommendations and develop a proposed solution to the problems identified. Importantly, in companies talking about high quality standards, trained, demanding the job, maximum productivity, among others, but where is the reciprocity of the firm to the worker?, Managers should take up the matter , to keep your most valuable resource, human resources, as it is the engine of the company and therefore deserves optimal conditions for their job performance, taking into account not only the economic, but rather incentives beyond a monthly payment for mere subsistence is why the present research, is to provide several alternatives for improving institutional performance, to motivate them to do a better job.